Intensi Pembelian Online Ditinjau dari Tipe Kepribadian Big Five pada Mahasiswa Fakultas Psikologi Universitas Prima Indonesia Medan - Elvinawanty, Rianda; Liza, Winda; Wong, Jeffrey; Putri, Yumelia; Citra, Yennie Chairani; Oktaviani, Adek (TAZKIYA Journal of Psychology, 2020)
Relationship between big five personality traits and online purchase intension was determined by this study. Researchers stated their hypothesis as follows : Big five personality could predict the intention of online purchase from the students who majoring in Psychology at Universitas Prima Indonesia Medan. There were 186 Psychology's students participating in this study and they was selected using purposive sampling technique. Assumption testing has been done by requirements test analysis including normality test, test of heteroscedasticity, also multicollinearity test. Data was analyzed using multiple regression analysis method through SPSS 16 version. Results of data analysis indicate the relationship between the Big Five Personality Trait and Online PurchaseIntention with the provement of the F value = 5,864 and the significancy value (p) = 0.000; (p<0.05). Results of this study showed that one of the five Big Five Personality dimension having correlation to Online Purchase Intention. It is the dimension of Openness to New Experience with significance (p) = 0.003; (p<0.05).